Fiqh al-Bī'ah and the Concept of Green and Blue Economy for Achieving Sustainable Development in the Context of SDGs - Latifah, Eny (Institut Agama Islam Negeri Ponorogo, 2024)
This study aims to explore existing literature on Fiqh al-Bī’ah's role in the Green and Blue Economy concepts to achieve Sustainable Development, specifically examining implementation, principles, roles, and objectives aligned with Maqāṣid al-Sharī‘ah. The literature review identified two primary themes: first, the SDGs' foundational principles within the green and blue economy frameworks, and second, Fiqh al-Bī’ah's viewpoint on these economic models. The findings demonstrate the enactment of green and blue economies through SDGs Principles, incorporating people as principal agents in upholding and executing the green and blue economy to realize SDGs across multiple facets, including environmental, social, economic, and legal governance; Planet, which entails diverse measures to safeguard the earth from degradation in terrestrial, marine, and aerial realms; Prosperity, highlighting efforts towards achieving prosperity through economic, social, and technological initiatives; Peace, emphasizing endeavors towards establishing peace, justice, and an inclusive society free from fear and violence, alongside securing environmental safety; and Partnership, involving collaborative efforts in global development with both government and non-government entities to maintain and conserve the environment. Additionally, Fiqh al-Bī’ah in the Green Economy is characterized by safeguarding the body and soul, aligning worldly and afterlife goals, ensuring balanced production and consumption, preserving ecosystem equilibrium, upholding the dignity of all beings, and humans fulfilling their stewardship on earth. The Blue Economy includes Zero Waste, ecosystem protection, promoting environmental cleanliness and friendliness, resource utilization efficiency, and encouraging social inclusiveness and employment creation.